Strategi Koperasi Unit Desa “Tani Makmur” dalam Peningkatan Kesejahteraan Masyarakat di Kalurahan Tirtonirmolo Kecamatan Kasihan Kabupaten Bantul - Naufal Abdi Hanan; Oktarina Albizzia (Sekolah Tinggi Pembangunan Masyarakat Desa APMD, 2021)
The problem of poverty is a problem which until now has not been able to be overcome by the central government in general and regional governments in particular. Various ways to overcome this problem have been taken by the government but this problem has not been able to be resolved. This poverty arises because there is a lack of tools to fulfill basic needs or difficult access to education and employment. Therefore, researchers are interested in conducting research with the title Unit Strategy of the Village Cooperative